Get Smart in Healthcare to Preserve the Power of Antimicrobials: Antimicrobial Stewardship - Reddy Kasarla, Rajeshwar; Choudhary, Sidhy; Verma, Aishwarya; Sharma, Ritesh; Pathak, Laxmi (Medical Journal of Eastern Nepal, 2024)
Antimicrobial resistance is one of the alarming health hazard to mankind. Unnecessary antibiotic usage leads to drug resistance, predisposes to opportunistic infections in immunodeficient and unnecessary economical loss to patient. This manuscript compiles & describes how crucial is Antimicrobial stewardship programs recommendations, strategies and implementation. Awareness and execution of institutional stewardship programs leads to better patient management, halt development of drug resistance and spread of resistant strains. This review is undertaken with an aim to discuss the development of an effective antimicrobial stewardship program and the key components and operating principles, and execution of these programs at healthcare facilities.